ChemoKnowings as Part of 21st Century Bildung and Subject Didaktik - Yavuzkaya, Merve; Clucas, Paul; Sjöström, Jesper (Frontiers in Education, 2022)
In this article, we elaborate the construct ChemoKnowings as subject-specific powerful knowings for chemical agency in the Anthropocene era. Related to constructs such as critical chemical literacy, ChemoCapabilities and eco-reflexive chemical thinking, we unpack the construct as an example of Carlgren’s powerful knowings, which relates Young’s powerful knowledge to the idea and tradition of Bildung. It means powerful knowledge containing embodied and relational (or tacit) dimensions. ChemoKnowings can therefore be described as embodied and relational knowledge in and about chemistry – (critical) chemical knowledge that matters meaningfully to the student, connecting them to themselves and the world, and conferring an ethical compass. By situating the teaching of ChemoKnowings within a vision for chemistry teaching as a part of a world-centered vision for schooling in the Anthropocene, ChemoKnowings are viewed as having the capacity to mobilise an ethico-socio-political action, that is, chemical agency. By focusing on student transformation of content for ChemoKnowings, and integrating elements of a theoretical didaktik model for eco-reflexive chemistry education, we develop a vision-oriented didaktik model for ChemoKnowings. More generally, we argue that didaktik models for supporting teachers’ consideration of student transformation of content for powerful subject-knowings is an important part of general subject didaktik. We present in the article vignettes that detail personal accounts for each of the three authors describing examples of chemistry-specific knowings that matter meaningfully to each of us, and which articulate our own embodied ethico-socio-political actions as students, teachers, researchers and consumers. Inspired by Klafki’s didaktik analysis, we end the article by proposing four areas of questions that the teacher can use in guiding their preparation and transformation of the content they bring into the classroom for promoting students’ ChemoKnowings, and thus Bildung in the 21st century.